Displaced masculinity : men, women and gender disorientation in contemporary Scottish fiction - Jones, Carole (Trinity College (Dublin, Ireland). School of English, 2005)
The subject of this thesis is the representation of gender in Scottish fiction since 1980. In writing of this period the stereotype of the Scottish 'hardman' gives way to portraits of uncertain and ineffectual male characters. The context of the thesis is the putative decline in patriarchal authority in society and a consequent destabilisation of gender which changes both women's and men's relationship with masculinity. This thesis is shaped, however, by a view of literature as not only a record of gender displacement and dislocation but as a space in which the effects of such displacement can be teased out and possible alternatives be explored. Consequently, the thesis deals with a range of writers, both male and female, positioned differently in terms of their treatment of gender, and of literary form, but all fundamentally concerned with issues of masculinity and with representation that goes beyond the confines of literary realism.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin